Digital rights during COVID-19 pandemic in Argentina, Brazil and Mexico - Bizberge, Ana (2020)
This article studies strategies, players, conditions and debates on digital rights during the COVID-19 pandemic in Mexico, Argentina and Brazil. The theoretical approach comes from the studies of communication as a fundamental human right and communication´s policies. The methodological approach proposes a comparative theoretical-normative and socio-political analysis. The lines of debate were the digital rights of access, privacy and freedom of expression. State policies varied depending on the political orientation of their authorities, pre-existing public policies, the specific policies adopted against COVID-19, and the competing forces of the players involved in each country. The companies developed regressive strategies from which, in certain cases, they had to reverse, also implemented some progressive but exceptional measures; while civil society and international organizations promoted progressive and long-term solutions.